IMPLEMENTATION OF THE HUMANISTIC-DEMOCRATIC MODEL IN IMPROVING STUDENTS' LEARNING MOTIVATION AND DISCIPLINE IN ELEMENTARY SCHOOLS - Wardana, Sasi Tari; Imaniar, Sabrina Kenia; Al Amin, Sazkiah Aulia; Dwisaputri, Sefia Jihan; Iskandar, Sofyan (LPPM Univ. Ibn Khaldun Bogor, 2026)
This study aims to examine the application of the humanistic-democratic model in an effort to improve student motivation and learning discipline in elementary schools. Education as the main foundation in the formation of quality human resources requires a comprehensive learning approach, not only oriented to the cognitive aspect, but also paying attention to the affective and social aspects. The humanistic model emphasizes respect for the uniqueness and potential of each individual, while the democratic model emphasizes the principles of equality, justice, and active student participation in the learning process. The method used in this study is a literature study with a content analysis of relevant literature related to the theory and practice of the humanistic and democratic models. The results of the study revealed that the application of the model is able to create an inclusive, warm, and conducive learning environment, which significantly increases student motivation and learning discipline. This approach is also effective in building students' character to be independent, responsible, and have social empathy from an early age. The implications of this study provide practical guidance for educators in developing holistic and humanity-oriented classroom management strategies in elementary schools.